(untitled) (مجلة العلوم الإنسانية والتطبيقية, 2019)
Core samples of Tanazeft Shale from two wells at Murzuq Basin were collected and analyzed in the Pyrolysis Rock Eval instrument for source rock evaluation includes source rock quality and quantity. The studied samples were collected from NC 115 and NC 174 blocks. The analysis results of total organic carbon (TOC) are the parameter that was used to determine organic matter (OM) richness of shale samples understudy and source rock type was identified as Kerogen type II .This was done by using the cross plot between both Hydrogen and Oxygen Indexes (HI & OI) of the sample results. All indications from sample results shoes that the lower part of Tanazefet Formation (Hot Shale Member) is a very good source rock while the upper part is a poor source rock. These analyses shoes also the kerogen type of the Hot Shale Member is type II which indicate oil prone stage.